Molecular and Virological Investigation of a Focal Chikungunya Outbreak in Northern India. (24th December 2013) - Soni, Manisha; Singh, Anil Kumar; Sharma, Shashi; Agarwal, Ankita; Gopalan, Natarajan; Rao, P. V. Lakshmana; Parida, Manmohan; Dash, Paban Kumar
Abstract : Chikungunya (CHIK) fever is one of the most important arboviral infections of medical significance. The objective of the present study is to identify and characterize the etiology of a focal febrile arthritis outbreak from Gwalior, northern India, during October-November 2010. A detailed virological (isolation) and molecular (end-point RT-PCR, quantitative RT-PCR, and nucleotide sequencing) investigation of this outbreak was carried out by collecting and studying 52 clinical samples and 15 mosquito pools from the affected region. The investigation revealed the presence of CHIK viral RNA in 29% of clinical samples and 13% mosquito pool by RT-PCR. The quantification of CHIK viral RNA in samples varied from 10 2.50 to 10 6.67  copies/mL, as demonstrated through quantitative RT-PCR. In addition, six CHIK viruses were isolated from RT-PCR positive samples. The nucleotide sequences of partial E1 gene of five representative CHIK viruses were deciphered, which revealed that all the viral strains from this outbreak belong to the recently emerging ECS African genotype. Identification of Chikungunya virus ECSA African genotype as the etiology of the present outbreak confirms the continued circulation of the novel genotype, since 2006, in India. The identification of CHIK virus in Aedes aegypti also confirmed it as the major vector in northern India.